Pengembangan E-Modul pada Materi Lingkaran Kelas XI Berbasis Etnomatematika Sawah Lodok Kearifan Lokal Masyarakat Manggarai - Alexandra Febriyanthy Agil; Wara Sabon Dominikus; Aleksius Madu (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The development of electronic learning media that is integrated with the diversity of local cultural wisdom in Indonesia in mathematics learning is a form of real innovation in response to the challenges of technological development and as a form of support for introducing Indonesian culture to the younger generation. Therefore, this study aims to develop an e-module on circle-related topics for Grade XI students based on the local wisdom of the Manggarai community's “sawah lodok” ethnomathematics, utilizing the Canva application. The research method employed is research and development using the ADDIE model. The stages of the ADDIE model include: 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. The data collection techniques used were interviews, questionnaires, literature reviews, and tests. The data analysis techniques in this study included validity analysis, practicality analysis, and effectiveness analysis. The research results indicate that the ethnomathematics-based rice field circle e-module is suitable, meeting the criteria for validity, practicality, and effectiveness. The average total validity of the e-module by three validators was 4.55, which falls into the highly valid category. The response from subject teachers, with an average response score of 4.88, falls into the highly practical category, while the response from the large student group was 4.05, which falls into the practical category. The percentage of student achievement in the large group was 88.8%, which falls into the highly effective category.